A nova norma regulamentadora n°20 como sistema de gestão em segurança de processo - Gré, Paula Lages (Universidade do Vale do Rio dos Sinos, 2013)
This article demonstrates the importance of updating the Regulatory Standard 20 (“NR-20”) (4), in supporting the prevention of major industrial accidents through the implementation of a Management System of Process Safety in medium and small industries in Brazil. The new NR 20 establishes minimum requirements for managing the risk factors of accidents involving activities with flammable and combustible liquids. The update of this standard has incorporated international rules, like the model of process safety management adopted in United States. And aims to encourage a prevention vision in companies, and provide a tool to support the implementation of a risk management system and not just a document to satisfy the inspection.
Keywords: Gerenciamento de riscos; Segurança de processo; Norma regulamentadora NR20; Acidentes ampliados; Inflamáveis; Líquidos combustíveis; Risks management; Process safety; Major accidents; Flammable; Combustible liquids; Regulatory standard NR20